In Utero Nutritional Manipulation Provokes Dysregulated Adipocytokines Production in F1 Offspring in Rats - Mervat Y. Hanafi; Mohamed I. Saad; Taha M. Abdelkhalek; Moustafa M. Saleh; Maher A. Kamel (Scientifica)
Background. Intrauterine environment plays a pivotal role in the origin of fatal diseases such as diabetes. Diabetes and obesity are associated with low-grade inflammatory state and dysregulated adipokines production. This study aims to investigate the effect of maternal obesity and malnutrition on adipokines production (adiponectin, leptin, and TNF-α) in F1 offspring in rats. Materials and Methods. Wistar rats were allocated in groups: F1 offspring of control mothers under control diet (CF1-CD) and under high-fat diet (CF1-HCD), F1 offspring of obese mothers under CD (OF1-CD) and under HCD (OF1-HCD), and F1 offspring of malnourished mothers under CD (MF1-CD) and under HCD (MF1-HCD). Every 5 weeks postnatally, blood samples were obtained for biochemical analysis. Results. At the end of the 30-week follow-up, OF1-HCD and MF1-HCD exhibited hyperinsulinemia, moderate dyslipidemia, insulin resistance, and impaired glucose homeostasis compared to CF1-CD and CF1-HCD. OF1-HCD and MF1-HCD demonstrated low serum levels of adiponectin and high levels of leptin compared to CF1-CD and CF1-HCD. OF1-CD, OF1-HCD, and MF1-HCD had elevated serum levels of TNF-α compared to CF1-CD and CF1-HCD (p<0.05). Conclusion. Maternal nutritional manipulation predisposes the offspring to development of insulin resistance in their adult life, probably via instigating dysregulated adipokines production.